Design and implementation of a national ecosystem assessment – insights from the French mountain systems' experience. Issue 1 (1st January 2019) - Crouzat, Emilie; Zawada, Mégane; Grigulis, Karl; Lavorel, Sandra
ABSTRACT: The French national ecosystem assessment (NEA), called EFESE for « Evaluation nationale des écosystèmes et des services écosystémiques » was launched in 2012 by the Ministry of Environment to comply both with European and national requirements. This paper reports on the design and implementation of the French NEA for high mountain systems, which (i) describes mountain ecological systems, (ii) characterizes the multiple ecosystem services they supply, and (iii) discusses the challenges and options related to sustainable governance of French mountain systems. Results highlighted the disproportional positive contribution of mountains to people's well-being, as well as their vulnerability to several drivers of change such as climate change or modification of agricultural practices. Based on the complete report, non-prescriptive key messages were provided as a summary for decision makers. This assessment was run as a participatory process, led by a core scientific working group and involving experts from academic, institutional and NGO structures. In this paper, we describe and discuss the design and implementation of the French mountain NEA and compare it to other international experiences. We believe our experience can support future NEA processes, in France and in other (inter)national settings.